2005
DOI: 10.1093/humrep/deh568
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the interstitial Cajal cells and the enteric nervous system in bowel endometriosis

Abstract: Endometriosis-induced damage of ICC, even before muscular infiltration, may cause bowel symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 35 publications
2
64
0
5
Order By: Relevance
“…9 Obstruction occurs as a result of (i) luminal stenosis (due to mural thickening and smooth muscle hyperplasia), (ii) disruption of Auerbach's plexus and the submucosal Meissner plexus and interstitial cells of Cajal and, (iii) inflammatory adhesions. 14 In a recent study of 89 patients with BE from the Mayo Clinic, preoperative confirmation was shown to be uncommon; colonoscopy with biopsy confirmed the diagnosis in 29.6% and only 15% of patients had histological lesions involving mucosa. 15 Endoscopic biopsies usually yield insufficient tissue due to involvement of deep layers of the bowel wall.…”
Section: Discussionmentioning
confidence: 97%
“…9 Obstruction occurs as a result of (i) luminal stenosis (due to mural thickening and smooth muscle hyperplasia), (ii) disruption of Auerbach's plexus and the submucosal Meissner plexus and interstitial cells of Cajal and, (iii) inflammatory adhesions. 14 In a recent study of 89 patients with BE from the Mayo Clinic, preoperative confirmation was shown to be uncommon; colonoscopy with biopsy confirmed the diagnosis in 29.6% and only 15% of patients had histological lesions involving mucosa. 15 Endoscopic biopsies usually yield insufficient tissue due to involvement of deep layers of the bowel wall.…”
Section: Discussionmentioning
confidence: 97%
“…Estas lesões podem ser assintomáticas, apresentarem sintomas semelhantes ao colon irritável ou em casos severos levarem até a obstrução intestinal 2,3 . É uma doença progressiva contínua, Koninckx et al (1991) 8 observaram que a incidência da endometriose profunda aumentava com a idade, sugerindo ser um doença progressiva e que havia associação da EPI com a dor pélvica.…”
Section: Discussionunclassified
“…A endometriose intestinal pode ocorrer em 5 a 27% das mulheres com endometriose, o reto e retossigmoide respondem por 70-93% das lesões intestinais 2 . Estas lesões podem ser assintomáticas, apresentarem sintomas semelhantes ao colon irritável ou em casos severos levarem até a obstrução intestinal 2 , 3 . Muitas mulheres com comprometimento intestinal sintomático também têm endometriose pélvica e queixam-se com freqüência de dismenorréia e dispaurenia.…”
Section: Introductionunclassified
“…2 The symptoms of bowel endometriosis closely simulates intrinsic bowel disease making diagnosis very difficult. 3,4 Hence awareness of this complex entity is essential to avoid misdiagnosis and unnecessary surgical intervention.…”
Section: Introductionmentioning
confidence: 99%